Integration of the Theory of Planned Behavior, Regulatory Pressures, Environmental Awareness, and Economic Perception in Influencing the Intention to Adopt Material Value Conservation Principles - Faris, Ahmad; Gabriel, Djoko Sihono; Nurcahyo , Rahmat (Enrichment: Journal of Multidisciplinary Research and Development, 2025)
This study investigates the key factors influencing the intention of plastic-based medical device manufacturers in Indonesia to adopt Material Value Conservation (MVC) principles in sustainable product design. Using the Theory of Planned Behavior (TPB) as a foundation, this research integrates environmental awareness, regulatory pressures, knowledge of MVC, perceived ease of adoption, and perceived economic value to develop a comprehensive analytical model. A quantitative survey was conducted with 70 manufacturers located in the Greater Jakarta area, and the data were analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM). The findings indicate that attitude, subjective norms, and perceived behavioral control have a significant direct effect on adoption intention, while regulatory pressure and knowledge of MVC influence intention indirectly through mediating constructs. Although environmental awareness and technical knowledge are high among respondents, perceived economic value remains the most significant barrier due to concerns over initial implementation costs. The study's novelty lies in its empirical extension of TPB within the context of circular economy adoption in the healthcare manufacturing sector. It provides practical implications for policymakers, particularly in low- and middle-income countries, to enhance sustainability through targeted incentives and regulatory frameworks. This research contributes to the academic literature by demonstrating the interaction between psychological, institutional, and economic variables in shaping green manufacturing intentions in an industry with high environmental impact.